Aligning intermediate climate targets with long-term decarbonisation ambition - Matthias Weitzel; Jose A. Ordonez (npj Climate Action)
The new submission round of Nationally Determined Contributions (NDCs) under the Paris Agreement presents a critical opportunity to enhance the credibility and feasibility of national decarbonisation pathways. By better aligning mid- and long-term targets, countries can reduce inconsistencies in emissions trajectories and strengthen the foundation for achieving long-term goals. Drawing on the experience of the European Union’s 2030 and 2040 intermediate emission targets, we highlight key considerations for setting milestones towards mid-century net-zero goals.